2017
DOI: 10.1111/bjd.15382
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human parvovirus B19 DNA in 22% of 1815 cutaneous biopsies of a wide variety of dermatological conditions suggests viral persistence after primary infection and casts doubts on its pathogenic significance

Abstract: As the virus has the capacity to persist in different tissues (including the skin) for long periods, it could represent merely an innocent bystander, so no pathogenetic significance can be inferred from the PCR positivity for B19V in the vast majority of dermatological conditions studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
1
22
0
1
Order By: Relevance
“…PCR-based studies have reported B19V genome in myocardial tissue of patients with myocarditis and dilated cardiomyopathy, however also in control cases, disproving the hypothesis that persistent myocardial viral infection might be a frequent cause of DCM or myocarditis [67][68][69]. Similar findings have been reported in skin samples from patients with dermatological diseases in which the role of viral infection is debated [70]. It should be considered that no biopsy tissue sample is blood-free.…”
Section: Parvovirus B19 and Myocarditis: Genetic Studies Unravel Molementioning
confidence: 72%
“…PCR-based studies have reported B19V genome in myocardial tissue of patients with myocarditis and dilated cardiomyopathy, however also in control cases, disproving the hypothesis that persistent myocardial viral infection might be a frequent cause of DCM or myocarditis [67][68][69]. Similar findings have been reported in skin samples from patients with dermatological diseases in which the role of viral infection is debated [70]. It should be considered that no biopsy tissue sample is blood-free.…”
Section: Parvovirus B19 and Myocarditis: Genetic Studies Unravel Molementioning
confidence: 72%
“…For B19V, a human‐specific pathogen, such evidence could be a temporal relation to seroconversion, as in the case of erythema infectiosum, or for the more complex chronic manifestations, viral gene expression exclusively in the diseased tissue. The paper by Santonja et al . is thus a good reminder for us all of the need to follow the modernized Henle–Koch postulates and to interpret our biological findings with caution.…”
mentioning
confidence: 87%
“…excellently reviewed the literature of B19V DNA detection in skin and studied as many as 1815 skin biopsies from 1749 patients with a wide variety of dermatological disorders, ranging from vasculitis to psoriasis . They detected B19V DNA in 402 (22%) skin samples of 394 patients with over 100 different clinical diagnoses (see Supplementary Table S1 in the paper by Santonja et al …”
mentioning
confidence: 99%
“…Viral DNA can be detected in liver, and in the heart the common presence of B19V DNA has raised attention on its potential role in the development of cardiomyopathies [42][43][44]. Viral DNA is commonly found in synovial tissues, thus with little informative content when trying to relate its presence to the development of rheumatologic diseases [27], and skin, with similar implication with respect to dermatological issues [45,46]. In all these instances, large-scale surveys have demonstrated the persistence of viral DNA in substantial fractions of sample populations, independently of clinical associations, so its mere detection cannot be assumed as a diagnostic criteria suggestive of a virus-driven pathological process.…”
Section: Virus Persistencementioning
confidence: 99%